Processes Underlying 50 Years of Local Forest-Cover Change in Yunnan, China - Jens Frayer; Daniel Müller; Zhanli Sun; Darla K. Munroe; Jianchu Xu (Forests, 2014)
Recognition of the importance of forests for local livelihoods, biodiversity and the climate system has spurred a growing interest in understanding the factors that drive forest-cover change. Forest transitions, the change from net deforestation to net reforestation, may follow different pathways depending on a complex interplay of driving forces. However, most studies on forest transitions focus on the national level rather than the local level. Here, case studies from 10 villages in Yunnan, China, are used to clarify the complex interactions among various pathways of forest transitions, derive insights on the underlying drivers that shaped the forest transitions, and determine the importance of changes in drivers over time. The results demonstrate that China's recent forest transition was caused by a range of interrelated pathways that were mediated by local circumstances. The degradation of forest ecosystem services caused by rampant deforestation and forest degradation created a scarcity of forest products and triggered state-initiated afforestation efforts, particularly in the 1990s, which continue to be important. More recently, economic development concomitant with smallholder intensification spurred reforestation, while the importance of state forest policy declined. The complexity of local land-use changes demonstrates the difficulty of identifying distinct transition pathways and calls for a more diverse approach that recognizes the interdependence of local processes.
Keywords: 330; forest transition; reforestation; agroforestry; land use change; China